Budget overruns experienced on tertiary institutional building projects – recourse to the contractors’ related factors - Adedokun, O.A.; Akinmusire, A.O.; Abiola-Ogedengbe, D. (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examined the contractors’ related factors that are causing budget overruns on tertiary institutional building (TIB) projects in south western part of Nigeria. Survey method was adopted and one hundred and twenty (120) questionnaires administered on the respondents. It was discovered that delay in delivery of materials to site, poor skills and experience of labour and financial problems, shortage of materials on site and lack of contractors’ staff on site were the bane of cost overrun experienced on construction projects. The study recommended adequate and timely planning in terms of providing schedule for ordering materials (both quantity and time) and the list of suppliers so as to avoid delay in delivery of materials to site. Experienced labours with adequate skills are to be used, while making readily available another source for financing the projects aside total dependency on monthly valuation to avoid financial difficulty. This study has served as eye opener to the critical CRF that should be accorded high priority to avert budget overruns.